COST LEADERSHIP STRATEGY, FIRM STRUCTURE AND PERFORMANCE OF STAR RATED HOTELS - NYOKABI, JANE (JOURNAL OF RESEARCH IN MANAGEMENT, 2019)
The purpose of this study was to assess the influence of cost leadership strategy and firm structure coalignment on firm performance of star rated hotels in Kenya. The research philosophy adopted was positivism and the research design was descriptive and correlative. The population consisted of senior managers from star rated hotels listed by the Tourism Regulatory Authority of Kenya as at 2018. Sampling techniques used in the study were proportionate stratified sampling and simple random sampling. 267 hotel managers were sampled. 253 managers responded out of which 103 respondents were found to represent cost leadership hotels. Hypothesis was tested using structural equation modeling. The study concluded that cost leadership strategy and firm structure coalignment has significant and positive influence on performance of star rated hotels in Kenya. The study recommends hotel managers to ensure a match between the pursuit of cost leadership strategy and the choice of firm structure.